Three new species of Thrasychiroides Soares & Soares, 1947 from Brazilian Mountains (Opiliones, Eupnoi, Neopilionidae) - Pinto-Da-Rocha, Ricardo; Bragagnolo, Cibele; Tourinho, Ana Lúcia (Zootaxa, 2014)
Three new species of the genus Thrasychiroides are described from the Brazilian Atlantic Rain Forest mountains: Thrasychiroides moporanga sp. nov. (type locality: Reserva Biologica de Alto da Serra de Paranapiacaba, State of São Paulo), T. toryba sp. nov. (type locality: São Francisco de Paula, State of Rio Grande do Sul) and T. ybytyra sp. nov. (type locality: Parque Nacional do Itatiaia, State of Minas Gerais). The male genital of Thrasychiroides brasilicus Soares & Soares, 1947 is illustrated for the first time. A remarkable structure on the penis of Thrasychiroides species is described and defined as pair of “arms”, also considered a putative synapomorphy of the genus.